Cγ1 Deficiency Exacerbates Collagen‐Induced Arthritis. Issue 7 (July 2016) - Strait, Richard T.; Thornton, Sherry; Finkelman, Fred D.
Abstract : Objective: IgG antibodies protect by aggregating pathogens and activating complement and stimulatory Fcγ receptors (FcγR). Although IgG1 accounts for a large percentage of murine serum antibodies, it poorly activates complement, binds more avidly to inhibitory FcγRIIb than to stimulatory FcγRIII, and has a relatively low aggregating ability. We previously demonstrated that IgG1 protects against complement‐ and FcγR‐independent renal disease by inhibiting immune complex obstruction of glomerular capillaries. The purpose of this study was to determine whether IgG1 also protects against the complement‐ and FcγR‐dependent disorder, collagen‐induced arthritis (CIA). Methods: CIA was induced by injecting mice with type II collagen (CII) (active model) or with IgG2a and IgG2b anti‐CII monoclonal antibodies (ArthritoMab) (passive model). Arthritis severity was assessed, and CII‐specific IgG was titered. Results: Cγ1‐deficient C57BL/6 mice lack IgG1 (IgG1 −/− ); in these mice, arthritis developed at a higher frequency and was more severe compared with IgG1 +/+ mice in the active model. Disease was FcγRIII‐ and C3‐dependent in both the IgG +/+ and IgG −/− mouse strains and was not influenced by interleukin‐4 receptor α in either strain. CII‐specific IgG2a/c titers were considerably higher in IgG1 −/− than in IgG1 +/+ mice and correlated with CIA incidence and severity. IgG1 +/+ mice that developed CIA had higher CII‐specific IgG1 and IgG2a/c levels than did those without CIA. CII‐inoculated BALB/c IgG1 +/+ and IgG1 −/− mice had much lower CII‐specific IgG2a/c titers than did C57BL/6 mice and failed to develop CIA but developed passive CIA when given ArthritoMab. Conclusion: The absence of a functional Cγ1 gene indirectly promotes the development of CIA, likely through increased production of IgG2a/c, an isotype that strongly activates complement and stimulatory FcγR.